THE CONSTITUTION IS A GUARANTEE OF HUMAN RIGHTS AND FREEDOMS. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article highlights that human rights are the highest value, that fundamental human rights and freedoms are protected and guaranteed by the state, and emphasizes that Uzbekistan remains firmly committed to its international obligations in the field of human rights.